How does democracy affect public debt? Evidence from the Arab world - Nouha Bougharriou; Walid Benayed; Foued Badr Gabsi (Kiel Institute for the World Economy (IfW), 2018)
This paper investigates the impact of democracy on public debt in the Arab world over the period 2002-2013. The results confirm the existence of an inverted-U relationship between democracy and public debt. This supports the hypothesis that some level of democracy is required to control public debt.
https://dx.doi.org/10.7910/DVN/68MATY
Keywords: H60; D72; 330; democracy; public debt; non-linear dynamic panel; arab world